Does Corporate Social Responsibility Affect Information Asymmetry? - Cui, Jinhua; Jo, Hoje; Na, Haejung (Journal of business ethics, 2018)
In this study, we examine the empirical association between corporate social responsibility (CSR) and information asymmetry by investigating their simultaneous and endogenous effects. Employing an extensive U.S. sample, we find an inverse association between CSR engagement and the proxies of information asymmetry after controlling for various firm characteristics. The results hold using 2SLS considering the reverse side of information asymmetry influencing CSR activities. The results also hold after mitigating endogeneity based on the dynamic panel system generalized method of moment. Furthermore, the CSR-information asymmetry relation is amplified in high-risk firms due to managers' efforts to build a good reputation. Last, we find that CSR engagement is inversely associated with reputational risk measure and lower predicted value of reputational risk is positively associated with lower information asymmetry measures. We interpret these results as supporting the stakeholder theory-based, reputation-building explanation that considers CSR engagement as a vehicle to build and maintain firm reputation thereby enhancing the information environment.